a)
[tex]3(x + y) - 5(2x + y + 1) = 3x + 3y - 10x - 5y - 5 = -7x - 2y - 5 \\\\ x =\frac{1}{13}, \ y = \frac{3}{8} \\\\ - 7\cdot \frac{1}{13} - \not{2}^1 \cdot \frac{3}{\not{8}_4} - 5 = - \frac{7}{13} - \frac{3}{4} - 5 = - \frac{28}{52} - \frac{39}{52} - 5 = - \frac{67}{52} - 5 = - 1\frac{15}{52} - 5 = - 6\frac{15}{52}[/tex]
b)
[tex]2x(x - y) - x(2x - 3y + 2)= 2x^2- 2xy- 2x^2+3xy- 2x=xy- 2x \\\\ x =-\frac{2}{3}, \ y =\frac{1}{3} \\\\ (-\frac{2}{3}) \cdot \frac{1}{3}- 2 \cdot (-\frac{2}{3})=- \frac{2}{9} + \frac{4}{3}=- \frac{2}{9} + \frac{12}{9}=\frac{10}{9}=1\frac{1}{9}[/tex]